The theory of life-cycle saving and investing - Zvi Bodie; Jonathan Treussard; Paul Willen (Federal Reserve Bank of Boston, 2007)
How much should a family save for retirement and for the kids' college education? How much insurance should they buy? How should they allocate their portfolio across different assets? What should a company choose as the default asset allocation for a mandatory retirement saving plan? We believe that the life-cycle model developed by economists over the last fifty years provides guidance for making such decisions. The theory teaches us to view financial assets as vehicles for transferring resources across different times and outcomes over the life cycle, and that perspective allows households and planners to think about their decisions in a logical and rigorous way. This paper lays out and illustrates the basic analytical framework from the theory in nonmathematical terms, with the aim of providing guidance to financial service providers, consumers, and policymakers.
Keywords: D14; D91; 330